(untitled) (Revista Peruana de Investigación Educativa, 2017)
This research focusses its attention in the field of mathematical and didactical teacher’s instruction; in this field, the teacher plays a fundamental role in the improvement of the teaching and learning process. From this point of view, this research informs and shows specific examples of the application of the didactical mathematical knowledge (DMK), in the analysis of the methodology of university mathematics lectures. This model is based on the theoretical-methodological tools of the Onto Semiotic Approach (OSA) to mathematical knowledge and teaching. This analysis adopts a qualitative perspective: descriptive and interpretative whit case study. The data sources are the transcriptions of the video recording of the math lectures where the professor discusses a specific mathematics topic: functions. This paper presents partial results regarding the application of the DMK model. These results show some characteristics of the professor’s lecture methodology. It has been evidenced some deficiencies in the professor’s knowledge, encouraging reflection on the knowledge required in the management of a professor’s teaching.